1993
DOI: 10.1212/wnl.43.1_part_1.41
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of antiepileptic medication in children–effects on cognitive function

Abstract: We present 100 children diagnosed with epilepsy who were seizure-free for more than 1 year and still on monotherapy of antiepileptic drugs (AEDs). We matched each child with a healthy classmate and performed neuropsychological testing and EEG before and after complete withdrawal of the AEDs. The withdrawal phase lasted 3 months, but the dose decrease was individualized for each patient. Three to 4 months after complete withdrawal of the drug all patients were reassessed. Patients with seizure relapse are exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
2
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(104 citation statements)
references
References 0 publications
4
90
2
8
Order By: Relevance
“…This persistent higher daytime sleep tendency could not be attributed to treatment or to seizure activity. The results of a large multicenter study based on AED discontinuation in children were reported by Aldenkamp et al (55). One hundred children who had been seizurefree for at least 1 year on a single AED were matched with healthy classmates.…”
Section: Studies In Patients Whose Medication Is Discontinuedmentioning
confidence: 99%
“…This persistent higher daytime sleep tendency could not be attributed to treatment or to seizure activity. The results of a large multicenter study based on AED discontinuation in children were reported by Aldenkamp et al (55). One hundred children who had been seizurefree for at least 1 year on a single AED were matched with healthy classmates.…”
Section: Studies In Patients Whose Medication Is Discontinuedmentioning
confidence: 99%
“…These studies reveal that the cognitive performance of epileptic children differs in comparison with control groups and it also differs between groups of epileptic children when different crisis types are studied: partial or generalized crises. [5][6][7] In view of the fact that cognitive functions involve attention and memory and that central auditory processing also involves attention and memory, we suspected that there could be performance differences in tests assessing CAP in epileptic patients with partial or generalized crises.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, poor academic achievement is widely reported in children with epilepsy, although many of these children have normal intelligence and stable intellectual ability (Bourgeois et al 1983, Seidenberg et al 1987. The influence of antiepileptic drugs (AEDs) on cognitive tasks has been discussed and is a topic of great interest in schoolchildren with epilepsy (Trimble 1990, Aldenkamp et al 1993.…”
mentioning
confidence: 99%